Evaluation of Objective Vitritis Grading Method Using Optical Coherence Tomography: Influence of Phakic Status and Previous Vitrectomy - Zarranz-Ventura, Javier; Keane, Pearse A.; Sim, Dawn A.; Llorens, Victor; Tufail, Adnan; Sadda, Srinivas R.; Dick, Andrew D.; Lee, Richard W.; Pavesio, Carlos; Denniston, Alastair K.; Adan, Alfredo; Adán, Alfredo; et al. (American journal of ophthalmology, 2016)
To evaluate a proposed method for objective measurement of vitreous inflammation using a spectral-domain optical coherence tomography (SD OCT) device in a large cohort of uveitis eyes, including pseudophakic eyes and vitrectomized eyes. Retrospective, observational cohort study. One hundred five uveitis eyes (105 patients) with different vitreous haze score grades according to standardized protocols and corresponding SD OCT images (Cirrus HD-OCT; Carl Zeiss Meditec, Dublin, California, USA) were included. Clinical data recorded included phakic status, previous vitreoretinal surgery, and anterior chamber (AC) cells and flare. SD OCT images were analyzed using custom software that provided absolute measurements of vitreous (VIT) and retinal pigment epithelium (RPE) signal intensities, which were compared to generate a relative optical density ratio with arbitrary units (VIT/RPE-relative intensity) and compared to VHS. VIT/RPE-relative intensity showed a significant positive correlation with vitreous haze score (r = 0.535, P < .001) that remained significant after adjusting for factors governing media clarity, such as AC cells, AC flare, and phakic status (R2-adjusted = 0.424, P < .001). Significant differences were also observed between the different vitreous haze score groups (P < .001). Preliminary observation did not observe differences in VIT/RPE-relative intensity values between phakic and pseudophakic eyes (0.3522 vs 0.3577, P = .48) and between nonvitrectomized and vitrectomized eyes (0.3540 vs 0.3580, P = .52), overall and respectively for each vitreous haze score subgroup. VIT/RPE-relative intensity values provide objective measurements of vitreous inflammation employing an SD OCT device. Phakic status and previous vitrectomy surgery do not appear to influence these values, although these preliminary findings need validation in future studies.